Have You Ever Been to Skarzysko? : A Survivor's Story - Celinski, Usher (Library of the Holocaust, 2012)
Intro -- Title Page -- Copyright -- Contents -- Translator's Foreword -- Before The Holocaust -- My Home -- My Brother is Called to the Army and Our Luck Turns Again -- A Good Polish Man Helped Us Open a Grocery Store -- Unadorned, Simple Jews -- Market Days in Skarzysko-Kamienna -- Youth Movements -- Social and Philanthropic Institutions -- Social Pursuits and Aspirations -- A Day in Skarzysko -- Evenings -- The War -- My Silent Wedding -- Yellow Patches in the Ghetto -- The Run to the East, To the Russian Side -- My Brother's Story -- An Auto-Da-Fe at Our Home -- Wierzbnik - Starachowice -- Germany Attacks the Soviet Union -- Slave Labor -- Jewish Life was Licentious -- Assassination through Hunger -- One of the Few -- The Jewish Police -- The Ghetto Struggled for Survival -- I Became a "Katzet Inmate" -- The "Economy" -- The Ten Murdered Martyrs -- Werke A -- I Received Twenty Lashes -- Business Merchants -- The Hospital -- Skarzysko Part Two -- A Jewish Betrayer -- I Saw My Parents -- Banishment from the Skarzysko Ghetto -- The Tragic Death of My Two Cousins -- The "King" in the Camp -- Female "Cousins" -- Without a Groszy -- "Experienced" Robbers -- No Place to Escape -- After the Jews Came the Polish People -- New Transports -- Twice On the Same Day I Was Saved From Death -- Delegation, International Committee of The Red Cross -- Spring on God's Universe -- 'Prominent' Jews -- A Baby Is Born In Camp -- A Heavenly Decree -- The Rape of Women -- New Barracks, Old Distress -- At the "Juden-Rein" Skarzysko -- I Work At Transporting Coal -- A New Camp Chief -- Gallows and Executions -- We Paid for the German Defeats -- The Last Time I Saw Miriam, My Sister -- Werke C -- Shop 13 -- Shop 58 -- Death and Amusement -- Grenades Stuffed With Sand -- What Will Happen With Us? -- In The Wagons -- Concentration Camp: Buchenwald -- What Awaiting Us Here?.